Effectiveness of group systematic desensitization in reducing test anxiety among college students - Tonogbanua, Sussette D. (Animo Repository, 1983)
The study develops, implements, and evaluates a group systematic desensitization program to reduce test anxiety among college students of St. Paul College, Manila. The subjects in the study were 26 fourth year Food and Nutrition students. The subjects were given a pretest using the Suinn test anxiety behavior Scale (STABS) two days before the program. Thirteen subjects were then randomly assigned to the experimental group and thirteen were assigned to the control group. The experimental group received the two day intensive group systematic desensitization program.Immediately following the program, the participants of the program were asked to evaluate the program of systematic desensitization to determine its effectiveness. A post test using the STABS were administered to the experimental and control groups 6 days after the treatment (2 days before the comprehensive examinations). A delayed post test using the same instrument was again administered to both groups 9 weeks after the program was conducted. A follow up evaluation questionnaire was administered to the experimental group together with the delayed post test. The t-test for dependent and independent samples was employed to compare the performance of both the experimental and control groups. Results showed that the subjects in the experimental group who received the training were able to demonstrate reduced test anxiety (p..01) while the untrained control group failed to demonstrate reduction in the test anxiety level. The results of the training indicate that the group systematic desensitization program was effective in reducing test anxiety. Results suggested further replication of the program on other students from different educational levels.